Scenario Computing for Analysis of Deep Uncertainty Systems - Y. Liu; Wang, G.; Wu, Z.; Fan, Z.; Y. Chen (Xitong Fangzhen Xuebao / Journal of System SimulationXitong Fangzhen Xuebao / Journal of System SimulationXitong Fangzhen Xuebao / Journal of System Simulation, 2018)
A method of scenario computing is developed for modeling systems with deep uncertainty. The method consists three complementary parts: hybrid modelling, diverse computing, and interactive validation. Hybrid modelling is to dynamically develop models with merging historical knowledges and observed information. Diversity computation is to simulate multiple plausible scenarios about system future. Interactive validation helps scenario computing process being on the right way instead of deviating. Two cases are provided in this paper applying scenario computing, one is earthquake and the other is driving and transportation. The results show good performance of scenario computing method in modeling uncertainty systems. © 2018, The Editorial Board of Journal of System Simulation. All right reserved.
Keywords: Deep uncertainty system; Diversity; Hybrid modelling; Scenario computing